2001
DOI: 10.1051/ejess:2001117
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structure and the performance of firms: Evidence from France

Abstract: Abstract. -This paper deals with the influence of ownership structure, variables of external and organisational discipline on financial and economic performance. By means of self-organising maps, in particular Kohonen maps, we highlight three main results. Firstly, the results obtained from a sample of French companies are consistent with the findings of Morck, Shleifer and Vishny (1988), McConnell and Servaes (1990) and Short and Keasey (1999) and suggest a non-linear relation between ownership structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
2
6
1
2
Order By: Relevance
“…The results may not reflect the actual situation. It is also consistent with what was found by researchers like (Severin, 2001;Kumar, 2003).…”
Section: H2: There Is a Significant Relationship Between Managerial Osupporting
confidence: 93%
See 1 more Smart Citation
“…The results may not reflect the actual situation. It is also consistent with what was found by researchers like (Severin, 2001;Kumar, 2003).…”
Section: H2: There Is a Significant Relationship Between Managerial Osupporting
confidence: 93%
“…This evidence was explained through "incentive and entrenchment integrated theory". Researchers also found conflicting results regarding managerial ownership as some found a positive relationship (Severin, 2001;Kumar, 2003). Others did not find that relationship (Demsetz & Villalonga, 1999;Rowe & Davidson, 2002;Long & So, 2002).…”
Section: Related Literature and Hypothesismentioning
confidence: 99%
“…Also; Thomsen and Pedersen (2000), Chen et al (2005), Vein Krivogorsky (2006), Cornett et al (2008 and Jaafar & El-Shawwa (2009) found a positive relation between ownership concentration and firm's performance. On the contrast; the study results disagree with the study of Severin (2001). Also; the result of this study is lined with Khamees et al, (2015).…”
Section: Empirical Analysis and Discussioncontrasting
confidence: 49%
“…Analiz sonuçlarına göre, özsermaye/aktifler oranının piyasa değeri üzerine istatistiksel olarak anlamlı düzeyde negatif etkisinin olduğu bulunmuş olup bu sonuç literatürdeki bazı çalışmalarla (Severin, 2001;Pagano vd., 1998;Yener ve Karakuş, 2012) paralellik göstermektedir. Aktiflerin yoğun bir şekilde özkaynaklar ile finanse edilmesi öncelikle Kıta Avrupası'nda bir fonlama yöntemi olup Anglo-Saxon kurumsal yönetim biçimine aykırılık göstermektedir.…”
Section: Sonuçunclassified